(untitled) (Palíndromo, 2021)
Exhibition in Palindrome Magazine - PPGAV-UDESC, inside the Dossier Artist’s writings and other propositions, curated by Raquel Stolf and Regina Melim, with the participation of 27 invited artists, and graphic design by Anna Stolf. The proposed call of the dossier – Artist’s writings and other propositions – seeks to gather investigations, propositions, and reflections around writing, reading and listening as processes, practices, procedures, and situations that catalyze, inscribe, and/or give body to artistic projects and their unfoldings, as well as that activate operations in these processes and practices. It is also proposed to address heterogeneous articulations between text and sound in the field of contemporary art and its intersections and/or reverberations with other contexts, in a relationship with other art spaces, with artist publishing practices, as well as writing processes in art research proposals.